2017
DOI: 10.1038/srep43320
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutagenesis in the medicinal plant Salvia miltiorrhiza

Abstract: CRISPR/Cas9 is a powerful genome editing tool that has been extensively used in model plants and crops, such as Arabidopsis thaliana, rice, wheat, and soybean. Here, we report the use of CRISPR/Cas9 to precisely knock out the committed diterpene synthase gene (SmCPS1) involved in tanshinone biosynthesis in Salvia miltiorrhiza, a traditional Chinese medicinal herb with significant pharmacological activities, such as vasorelaxation, protection against ischemia-reperfusion injury, and antiarrhythmic effects. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…Li et al . () used CRISPR/Cas9 techniques that targeted the committed diterpene synthase gene ( SmCPS1 ) involved in tanshinone biosynthesis in Salvia miltiorrhiza , and different tanshinone accumulation levels were detected in chimeric and homozygous mutants. Therefore, these results suggested that SmCPS1 in chimeric mutants was knocked down instead of being knocked‐out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al . () used CRISPR/Cas9 techniques that targeted the committed diterpene synthase gene ( SmCPS1 ) involved in tanshinone biosynthesis in Salvia miltiorrhiza , and different tanshinone accumulation levels were detected in chimeric and homozygous mutants. Therefore, these results suggested that SmCPS1 in chimeric mutants was knocked down instead of being knocked‐out.…”
Section: Discussionmentioning
confidence: 99%
“…Both GABA-2 (CR-GABA-20) and GABA-3 (CR-GABA-56) mutants were chimeric ( Figure S3), and chimeric mutations might not result in the complete loss of gene function, and the GABA-TP enzyme activity in the fruits of these two GABA mutants remained although the level was significantly lower than that of WT plants (Figure 8). Li et al (2017) used CRISPR/Cas9 techniques that targeted the committed diterpene synthase gene (SmCPS1) involved in tanshinone biosynthesis in Salvia miltiorrhiza, and different tanshinone accumulation levels were detected in chimeric and homozygous mutants. Therefore, these results suggested that SmCPS1 in chimeric mutants was knocked down instead of being knocked-out.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 2017 [65] Salvia miltiorrhiza phenolic acid biosynthetic pathway rosmarinic acid synthase gene (SmRAS) CRISPR/Cas9 Zhou et al 2018 [66] Solanum lycopersicum…”
Section: Crispr/cas9mentioning
confidence: 99%
“…CRISPR/Cas9 is a gene-editing tool gaining popularity in recent years. Li et al [72] knocked out the committed diterpene synthase gene (SmCPS1) involved in tanshinone biosynthesis in S. miltiorrhiza by CRISPR/ Cas9. The metabolomic analysis revealed that tanshinones, especially cryptotanshinone, TA-IIA and tanshinone I, are completely missing in homozygous mutants, without influencing other phenolic acid metabolites.…”
Section: Transgenic Plant Materialsmentioning
confidence: 99%